One-Year Clinical Outcome and Risk Factor Analysis of Directional Atherectomy Followed With Drug-Coated Balloon for Femoropopliteal Artery Disease. (December 2021) - Feng, Zibo; Yang, Shuofei; Sang, Hongfei; Xue, Guanhua; Ni, Qihong; Zhang, Lan; Zhang, Wei; Fang, Xin; Ye, Meng
Purpose: This study investigated the 1-year clinical outcomes of directional atherectomy combined with drug-coated balloon (DA + DCB) in femoropopliteal artery disease (FPAD) from real-world experience. Materials and Methods: A retrospective study was conducted of patients treated between July 2016 and June 2019 using DA + DCB for FPAD. Patients' demographics, comorbidities, clinical characteristics and outcomes, and angiography and duplex ultrasound findings were analyzed. The 6-month and 1-year primary patency, primary assisted patency, secondary patency, and freedom from clinically-driven target lesion revascularization (CD-TLR) were evaluated. Univariate and multivariate analyses were performed to identify risk factors of primary patency loss or CD-TLR. Results: Seventy-nine consecutive patients (83 lesions, mean age 70.9 years, 52 men) were included. Twenty-seven limbs had lifestyle-limiting claudication and 56 limbs had critical limb ischemia. There were 73 and 10 limbs with de novo lesion and in-stent restenosis, respectively. The mean lesion length of all the patients was 22.1 cm. The mean length of chronic total occlusions (CTOs) was 8.3 cm. Severe calcification was found in 32.5% cases. The 1-year primary patency rate was 80.8% and freedom from CD-TLR was 92.2%. The bailout stenting rate was 2.4%. Patients with CTO >10 cm had significantly lower 1-year primary patency rate and freedom from CD-TLR than did patients with CTO ≤10 cm. Total length of CTO (stratified as ≤5 cm, 5–10 cm, >10 cm) was identified as an independent risk factor of 1-year primary patency loss and CD-TLR. Conclusion: DA + DCB appears to be a safe and effective endovascular therapy to treat FPAD in real-world clinical practice, with a promising 1-year patency rate with a low rate of bailout stenting.